An Assessment of Health Services Contracting in Mexico's Seguro Popular de Salud, 2006–2014. Issue 4 (2nd October 2017) - González-Robledo, Luz María; Nigenda, Gustavo; García-Saiso, Sebastián
Abstract: Abstract— The introduction of Seguro Popular de Salud (SPS) expanded the practice of contracting in the Mexican health system. Specifically, SPS established that formal relationships among institutional agencies should be mediated by written agreements and contracts. These contracts were supposed to ensure a technically sound interaction between financing and service provision agencies. This study aims to assess the degree to which the contracts adhere to five characteristics of cost-effective contracting proposed by Figueras et al. Information was extracted from a purposive sample of 30 institutional agreements and contracts formalizing the relationship among federal, state, and local public agencies and between public and private agencies. Contracts and management agreements were obtained from of a series of SPS evaluations carried out between 2007 and 2012 (including some agreements signed in 2006); additional contracts signed after 2012 were obtained through an Internet search. Most of the five framework characteristics were identified in the sample of contracts, but certain elements such as pay-for-performance and the explicit definition of the volume of services to be provided were clearly deficient. This analysis found that over time SPS contracts have been modified to better establish inter-institutional relationships in compliance with guidelines regarding the allocation of funds and the purchasing of services, but they still need further improvements to accomplish their role of increasing efficiency in the flow of funds through the Mexican health system.